Forces in swimming--a re-evaluation of current status - Rushall, B. S.; Sprigings, E. J.; Holt, L. E.; Cappaert, J. M.
ABSTRACT The development of thinking and research over the past 25 years for understanding the basic properties of force production in swimming strokes is discussed. The limitations and deficiencies of Bernoulli's Principle for being the sole explanation for propulsive forces are presented. Bernoulli's Principle is simply too limited and inappropriate for accounting for observed and measured phenomena in competitive swimming strokes. Lift forces have been shown to be minor in the propulsive phases of the crawl, back, and butterfly strokes. In breaststroke, both drag and lift forces are recorded in the inward and outward-sculling phase of the stroke. However, drag forces are not in a facilitatory direction and so forward propulsion results from lift created by an exaggerated angle of attack (when compared to those exhibited in crawl, back, and butterfly strokes), and a large canceling of the effect of the mostly symmetrical drag forces. The dominance and importance of lift forces in breaststroke is not a justification for promoting Bernoulli's Principle as the foundational reason for propulsion. Drag forces are dominant and in a facilitating direction during propulsion in crawl, back, and butterfly strokes. The extent of their importance is markedly more than any lift force contribution. Several practical considerations were drawn from the assertions made to date. They will require a change in the teaching/coaching emphasis of many practitioners who promote an exaggeration of the S-shaped pull, that is, they believed that large sideways movements are beneficial for propulsion. A greater emphasis should be placed on orienting swimmers to focus on the role of the forearm in propulsion, particularly at higher speeds. Three forms of resistance are proposed for consideration. They have practical implications for coaches. Shaving and wearing a suit with a fabric that has a low coefficient of resistance can reduce frictional drag. Maintaining streamlined positions during the entirety of all strokes can minimize form drag. Removing any unnecessary vertical and all lateral and exaggerated movements can minimize Wave drag. Attention to the details of drag reduction is most important when speed of swimming is emphasized. The production of force is important. However, resistance increases at a much greater rate than changes in speed due to propulsive forces. Thus, it is advocated that swimming actions first should be oriented to minimizing resistance, and second, to developing propulsion as long as positions that minimize resistances are maintained. A change in entrenched thinking with regard to propulsive and resistive forces is warranted. When that change is made and its importance introduced into coaching, swimmers' performances should improve. PART II - CURRENT STATUS https://coachsci.sdsu.edu/swim/bullets/forces2.htm PART III - PROPULSIVE FORCES https://coachsci.sdsu.edu/swim/bullets/forces3.htm PART IV - RESISTIVE FORCES https://coachsci.sdsu.edu/swim/bullets/forces4.htm